Periodate Inhibition of Transformation and Competence Development in Haemophilus influenzae - Ranhand, Jon M. (1966)
Ranhand, Jon M. (University of Cincinnati, Cincinnati, Ohio), and Herman C. Lichstein. Periodate inhibition of transformation and competence development in Haemophilus influenzae. J. Bacteriol. 92:956–959. 1966.—Periodate treatment of competent cells reduced the frequency of transformation to streptomycin resistance about 90% while reducing cell viability about 30% or less. Moreover, when periodate was added to cells early in the competence-development phase, these, too, were unable to develop maximal competence. Periodate inhibition was dependent on time and concentration as well as on the composition of the suspending menstruum. Periodate had no effect on transforming deoxyribonucleic acid (DNA), nor did it prevent transformation when added to competent cells which had already reacted with DNA. Furthermore, the progeny from cells inactivated 90% could be made fully competent, showing that the inhibition was not genetic. It was concluded that the periodate-sensitive substrate may involve the DNA binding site(s).